An herbarium for Florbela: root, color, leaf and flower of Alentejo’s heathland (Simbiótica. Revista Eletrônica, 2022)
This paper intends an ecocritical approach to the perceptions of the Alentejo landscape in Florbela Espanca’s prose and poetry, shifting the focus from the subject’s voice to the geographical and ecological context of exterior landscape. Particularly, it aims to collect, analyse, and reorganize, under the metaphor of an Herbarium litterarium, the plant specimens of the heathland, to glean the memory of a natural habitat that has now almost disappeared from Alentejo. I suggest a new reading of the texts as a documental source for understanding the ecological values of ​Alentejo’s heathland at a time of transformation of the autochthonous landscape. We discover, in the author’s texts, a multi-sensory and phenomenological encounter with the landscape. The article concludes that Florbela’s organic and immersive writing configures the illustration of the concepts defended nowadays by ecophenomenology.Keywords: Alentejo; heathland; Florbela Espanca; landscape.